Divalent Cations in Native and Reaggregated Mycoplasma Membranes - Kahane, Itzhak (1973)
The Mg(2+) content of membranes of several Mycoplasma and Acholeplasma species varied between 0.88 and 1.98 μg of Mg(2+) per mg of protein, depending on the species and on growth conditions. Ca(2+) could be detected only when it was added to the growth medium. The Mg(2+) content of isolated A. laidlawii membranes could be increased almost threefold by dialysis against 20 mm Mg(2+), whereas aggregated A. laidlawii membranes contained about six to eight times more Mg(2+) per mg of protein than the native membranes. This was taken to indicate that the molecular organization of the lipid and protein in the reaggregated membranes differs from that of the native membranes. Between 60 and 83% of the Mg(2+) in native and reaggregated A. laidlawii membranes was associated with the lipid fraction extracted with chloroform-methanol. The removal of over 80% of membrane protein by Pronase digestion did not release any significant amount of Mg(2+). Hence, most of the divalent cation appears to be bound to membrane lipids, most probably to phospholipids. Ethylenediaminetetraacetic acid released the bulk of Mg(2+) bound to the native and reaggregated A. laidlawii membranes, except for about 0.5 μg of Mg(2+) per mg of protein which was too tightly bound. Hence, a small but fairly constant amount of Mg(2+) is unavailable for chelation.